2011
DOI: 10.1007/s11249-011-9817-3
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Wear Process Before and During Scuffing in Sliding Contact

Abstract: In this study, a direct observation of a point contact area was conducted to understand the scuffing phenomenon. The contact area was produced between a rotating sapphire disc and a stationary steel ball and it was lubricated using n-hexadecane. The image detected by a colour digital CCD camera, load, and friction were synchronously recorded by a computer during the test. It was found that wear debris produced in the contact area played an important role in the wear process, which includes running-in and scuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Enthoven et al further proposed that scuffing is caused by a critical rate of production of wear particles and its accumulation in the inlet of the lubricated contact. Our previous study on in-situ observation of scuffing process of steel [5] also indicated that wear particles produced in the contact area plays an important role in the scuffing process. Nikas's numerical simulation [6,7] showed that the presence of soft and ductile particles in lubricated contacts can cause surface softening/melting and local scuffing.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Enthoven et al further proposed that scuffing is caused by a critical rate of production of wear particles and its accumulation in the inlet of the lubricated contact. Our previous study on in-situ observation of scuffing process of steel [5] also indicated that wear particles produced in the contact area plays an important role in the scuffing process. Nikas's numerical simulation [6,7] showed that the presence of soft and ductile particles in lubricated contacts can cause surface softening/melting and local scuffing.…”
Section: Introductionmentioning
confidence: 86%
“…Each frame of the contact images was precisely synchronized with friction coefficient data. Instrumentation of this tribometer is described in [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sand contamination of lubricated gear wheels not only causes accelerated wear by abrasion but also a temperature rise in the lubricant due to elevated friction, which is associated with increased roughness and more extensive metallic contact between the gear teeth [142]. Wear particles generated in lubricated sliding contacts also play an important role in controlling the onset of scuffing [141]. The critical temperature appears therefore to be a function of many parameters not just pressure, heat of adsorption and sliding speed.…”
Section: · Mixed Lubrication and Scuffingmentioning
confidence: 99%
“…The authors developed in situ observation systems for the contact area comprising a rotating sapphire disc and a stationary steel pin. Yagi et al [36] directly observed the contact area, reporting local plastic flow on the steel surface during scuffing. Li et al [37] indicated that plastic flow firstly occurred at the point where the wear particles accumulated.…”
Section: Introductionmentioning
confidence: 99%